Acid Violence Against Women: Bangladesh Perspective - Kabir, Md. Humayoun; Sayeed Munna, Md. Abu; *, Md.Sanaulla; Alam, Dr. Tasnim (IJRDO - Journal of Social Science and Humanities Research, 2017)
This study tries to present the existing acid violence against the women of Bangladesh which has revealed the vulnerability of the women in our society. From birth to death, women become victims of various kinds of discrimination and violence. Acid violence is one of them. This write up is actually aimed at creating and help increasing awareness regarding the violence against women and guiding all from commoners to the policy makers to prevent them from this specific violence. In this connection, this article attempts to search out the ways and means of how the acid violence against women can be combated from the society and the paper at its conclusion suggested some remedial recommendations for adoption.